Diversifikasi Produk Wisata Sebagai Strategi Pengembangan Daya Saing Wisata Kota Batu - Sukmaratri, Myrna; Damayanti, Maya (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Although it is a new city, the economic growth of Batu City quite rapidly, especially in the tourism sector. The variety of tourism potential bring tourism sector of Batu City become competitive in provincial even national level. However, along the friction of tour base, there are indication relate of tourist saturation in Batu City. It was shown from decrease in number of tourists in the year 2009-2012 with an average of 13% annually. In addition, the rapid development of tourism in Batu City suspected caused some negative impact on the environment. Therefore, efforts to build the tourism sector in Batu City forward has been duly implementing the concept of sustainable tourism, which one of them is by diversification of tourism products. Diversification of tourism products divided into two, namely destinations and attractions. To diversify destinations Batu City is directed to build the tourist market in corridor Diponegoro and Gajah Mada street around Alun-alun Batu City. Meanwhile, the diversification of tourism products for the natural attractions is directed into the development of alternative tourism with travel packages. In artificial attractions, besides the addition of themed rides, managers can diversify tourist attraction by adding a cultural event such as dances at certain hours. Besides that, diversification of tourism products can be done with the addition and improvement of tourism facilities as well as increased accessibility. It can be directed by a central parking and tour transportation as well as the construction of new access by railway from Abdurrahman Saleh Airport to Batu City passing through Malang City.